Labour market integration for refugees: A social justice framework - Tamara Kool; Zina Nimeh (United Nations University (UNU), Maastricht Economic and Social Research Institute on Innovation and Technology (UNU-MERIT), 2024)
This paper examines the labour market engagement of protracted refugees. Despite international guarantees for the right to work, many refugees face legal and bureaucratic barriers, leading to exclusion from host communities and over reliance on diminishing humanitarian aid. By synthesizing literature on labour market participation of refugees against the backdrop of social justice theories, and taking a social exclusion angle, the paper constructs a conceptual framework for a better understanding of labour market engagement that includes both formal and informal sectors. It highlights the need for policies that support agency and self-reliance for refugees.
Keywords: J47; J48; J68; J78; O15; Z18; 330; Refugee Labour Market; Social Justice; Social Exclusion; Agency